The outcome of continuous assessments on undergraduate pharmacy students' performance - May, Khin Soe; Tin, Myo Han (Malaysian Pharmaceutical Society, 2012)
Mid semester examination (MSE) was abolished and replaced by continuous assessments (CA) in Kulliyyah of Pharmacy, International Islamic University Malaysia at 2010. The overall score of CA and MSE contribute 40% of total score. This study examined the outcome of CA on the students’ academic performance in Medical Biochemistry. We studied the impact of CA on overall students’ performance before and after curriculum changes. A retrospective desktop study was done by using the records of students’ performance. Total 373 students from two different groups were included. Group I consisted of 175 students who had taken the MSE under the old curriculum whereas Group II consisted of 198 students. Both groups received the same structure of questions for the end semester exam (ESE). The comparative analyses of scoring in CA versus MSE and a cross analysis of final grading in accordance with academic years were done. Group II achieved better results with CA (27.91±3.28) than group I (23.91± 3.41) with MSE [p <0.05]. The ESE result in group II (67.84±7.2) was significantly higher than that of group I (61.56±8.52) [p<0.05]. Total 8 students (4.6%) from group I failed but no failure from Group II. Thus, CA assists the students in improving their grades at the ESE. This CA is not favored by the students as they have to work hard to meet the commitments and has more credibility than MSE in evaluating students’ study progress. Thus, the new system of assessment (CA) is more applicable and beneficial than previous MSE for students.